THE ANALYSIS OF STUDENT MISCONCEPTIONS ON ESSAY QUESTIONS BASED CHEMICAL EQUILIBRIUM LESSON WITH IN DEPTH INTERVIEW - Silviana, Messy; Ritonga, Soleman (Universitas Negeri Surabaya, 2025)
Lack of students' understanding of the concept of chemical equilibrium causes many misconceptions to occur. Chemical equilibrium is one of the topics in chemistry that consists of various concepts that are interconnected, sequential, and organized, so it is often considered complex and causes misconceptions. This study aims to analyze students' misconceptions on the topic of chemical equilibrium and determine its percentage. This study used a mixed method with an explanatory sequential design. The subjects of the study involved 30 students of class XI Tahfiz SMA IT Fadhilah Pekanbaru. The data collection instrument was in the form of essay questions with a reliability coefficient of 0.814 and empirical validity showed 10 valid questions and 3 invalid questions. Data analysis techniques were carried out after collecting test results, including data processing and interpretation to identify misconceptions. The results showed that 17% of students from the total sample had misconceptions. The lowest misconception occurred in indicator (10), namely determining the direction of equilibrium shifts influenced by temperature, with a percentage of 3.33%. Meanwhile, the highest misconception was found in indicator (8), namely determining the direction of equilibrium shift influenced by concentration, with a percentage of 46.67%. Based on these results, it is concluded that the misconceptions that occurred in the sample were in the low category. This shows that the learning method used is quite effective in improving conceptual understanding.